Supporting Multi-level Medical Education with Knowledge-Based Systems - King, K.; Carstairs, M. (Methods of Information in Medicine, 1997)
Knowledge-based systems for medicine have enjoyed minimal success in developing countries as end-user systems. The reasons for this are complex. As funding agencies understandably tend to err on the side of caution, and knowledge-based systems are still (despite an almost 40 year history) seen as a new and untried technology, few have been implemented. Of those which have, most are inappropriately simple and thus do not fit in with the real-life clinical environment. In contrast to the sophisticated systems in use in developed countries which reflect a mature technology, the use of knowledge-based systems in medicine in developing countries has primarily revolved around simple ‘expert’ systems, where the program functions more as a ‘guru’ than as a support function. We propose the more appropriate use of these systems as educational tools in medicine. In this discussion paper we describe a multi-level programme to support medical education, focusing on patient information systems involving natural language generation, decision-support systems as educational aids for primary health-care workers and model-based reasoning tools which allow exploratory learning for physicans in training. Throughout this paper we refer to Knowledge-Based Medical Education Systems as KBMES.
Keywords: Medical Education; Knowledge-Based Systems; Developing Countries